2013
DOI: 10.1002/app.39741
|View full text |Cite
|
Sign up to set email alerts
|

Lightly branched poly(vinyl alcohol) for fluid loss additive

Abstract: One kind of branched Poly(vinyl alcohol) has been synthesized via common radical copolymerization of vinyl acetate in methanol by adding a bifunctional monomer Allyl methacrylate (AMA) followed by saponification. The comonomer AMA has two reactive double bonds that can provide the branching points to macromolecule chain structure. With these reactive points, the copolymer with long chain branches can be obtained. The long chain branches bring the copolymer higher viscosity by the entanglement of them between m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…The characteristic peaks of Cl 2p (Figure 3e) at 199.48 and 197.88 eV were attributed to Cl − Cl 2p 1/2 and 2p 3/2 50 . In addition, the peaks at 529.78 and 531.78 eV binding energies in the O 1s spectrum of Figure 3f corresponded to the bond of BiO in the BiOCl lattice and the TiO bond in TiO 2 , respectively 51,52 . Comparison of the XPS of TiO 2 /PAN (Figure S1) reveals that the peaks of Ti 2p 1/2 shift toward high binding energy, and the peaks belonging to the OTi bonds in O 1s shift toward low binding energy, then, combined with the XRD, we can conjecture that there is an interaction between BiOCl and TiO 2 .…”
Section: Resultsmentioning
confidence: 94%
“…The characteristic peaks of Cl 2p (Figure 3e) at 199.48 and 197.88 eV were attributed to Cl − Cl 2p 1/2 and 2p 3/2 50 . In addition, the peaks at 529.78 and 531.78 eV binding energies in the O 1s spectrum of Figure 3f corresponded to the bond of BiO in the BiOCl lattice and the TiO bond in TiO 2 , respectively 51,52 . Comparison of the XPS of TiO 2 /PAN (Figure S1) reveals that the peaks of Ti 2p 1/2 shift toward high binding energy, and the peaks belonging to the OTi bonds in O 1s shift toward low binding energy, then, combined with the XRD, we can conjecture that there is an interaction between BiOCl and TiO 2 .…”
Section: Resultsmentioning
confidence: 94%
“…In particular, a cross-linking technique was utilized to form a solid polymeric network dispersed in a material matrix. In previous research, cement-based materials showed an obvious retarding side effect when using cross-linked PVA polymers for filming effect [6,8,16,22]. However, the cross-linked network was stable with higher mechanical strength.…”
Section: Introductionmentioning
confidence: 93%
“…Dias et al [7], Han and Zhang [8], and Cui et al [9] depicted that molecular structure characteristics of the polymeric fluid loss additive were the key points to improve fluid loss additive application effectiveness. Salami and Plank depicted that the highly dispersed grafting polymer structure was beneficial to overcome unnecessary side effects when contacting with electrolyte matters, such as metal ions [10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such additives include inorganic fine particles and polymer fluid loss additives [3,4]. These additives include polyvinyl alcohol film-forming fluid loss additives and polycarboxylic acid fluid loss additives; currently, the latter is most widely used [5,6]. Although carboxylic acids serve as key functional groups for water loss during take-off and landing, previous research shows that this group of fluid loss additives induces strong thickening and retarding side effects [7,8].…”
Section: Introductionmentioning
confidence: 99%